(untitled) (Journal of Dhaka Medical College, 2015)
Cancer, till date stands rigidly unconquered despite most strenuous effort and relentless endeavor by the scientists around the world. In global terms Oral cancer is among the most common malignancy and represents one of the greatest management challenges for the otolaryngologists as well as by the head and neck surgical oncologists. Besides accumulation of genetic mutations, numerous other carcinogens including viral and chemical are well studied and documented. However, in the oral cavity, the role of microbiota in carcinogenesis is not known. Microbial populations on mouth mucosa differ between healthy and malignant sites, and certain oral bacterial species have been linked with malignancies, but the evidence is still weak in this respect. Nevertheless, oral microorganisms inevitably upregulate cytokines and other inflammatory mediators that affect the complex metabolic pathways, and may thus be involved in carcinogenesis. Poor oral health also associates statistically with prevalence of many types of cancer such as pancreatic and gastrointestinal cancer. This review presents commonly implicated bacteria in oral carcinogenesis, and their role in cancer therapeutics as well. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21545 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 211-215